2006
DOI: 10.1093/annonc/mdl114
|View full text |Cite
|
Sign up to set email alerts
|

Response to neoadjuvant chemotherapy in lobular and ductal breast carcinomas: a retrospective study on 860 patients from one institution

Abstract: ILC appeared less responsive to chemotherapy but presented a better outcome than IDC. While new information on biological features of ILC is needed, we consider that neoadjuvant endocrine therapy in hormone receptor-positive ILC may be a more adapted approach than neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
111
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(124 citation statements)
references
References 25 publications
10
111
0
3
Order By: Relevance
“…Patients diagnosed with lobular invasive carcinomas were significantly older (Sastre-Garau et al, 1996) Because of the frequent use of either exclusive or preoperative radiotherapy, the study of pathological response in our series was not relevant. Bearing in mind the mandatory caution in interpreting clinical response (Bollet et al, 2007), we found that the response to primary chemotherapy was significantly better for ductal invasive carcinomas than for lobular (X50% of clinical response in 60% for ductal vs 47% for lobular; P ¼ 0.04), confirming the notion developed by others that lobular carcinomas responded less than ductal carcinomas to neoadjuvant chemotherapy (Mathieu et al, 2004;Cristofanilli et al, 2005;Tubiana-Hulin et al, 2006;Wenzel et al, 2006;Katz et al, 2007). However, in the present study, in multivariate analysis, only high grade was significantly associated with a higher rate of clinical response.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Patients diagnosed with lobular invasive carcinomas were significantly older (Sastre-Garau et al, 1996) Because of the frequent use of either exclusive or preoperative radiotherapy, the study of pathological response in our series was not relevant. Bearing in mind the mandatory caution in interpreting clinical response (Bollet et al, 2007), we found that the response to primary chemotherapy was significantly better for ductal invasive carcinomas than for lobular (X50% of clinical response in 60% for ductal vs 47% for lobular; P ¼ 0.04), confirming the notion developed by others that lobular carcinomas responded less than ductal carcinomas to neoadjuvant chemotherapy (Mathieu et al, 2004;Cristofanilli et al, 2005;Tubiana-Hulin et al, 2006;Wenzel et al, 2006;Katz et al, 2007). However, in the present study, in multivariate analysis, only high grade was significantly associated with a higher rate of clinical response.…”
Section: Discussionsupporting
confidence: 81%
“…The lower rate of breast conservation in lobular vs ductal invasive carcinoma could also be due to the larger size of ILC. The most striking data are the high rate of breast conservation for both ductal and even more so for lobular carcinomas when compared to the rates in the literature that range, respectively, between 30 -48 and 16 -31% (Mathieu et al, 2004;Cristofanilli et al, 2005;Tubiana-Hulin et al, 2006). This is explained in our series by the use of either exclusive or preoperative radiotherapy, particularly for large tumours with a poor response to neoadjuvant chemotherapy and, therefore, more frequently for lobular (40%) than for ductal (26%) carcinomas.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, the outcome of ILC appeared to be more favorable than for IDC [20]. Since primary chemotherapy might not achieve main objectives of this strategy such as breast conserving surgery and pCR, its use in ILC was questioned [22]. The results of the present study support the hypothesis that the degree of endocrine responsiveness rather than the histotype should be considered in the selection of patients candidate to preoperative therapy.…”
Section: Discussionmentioning
confidence: 52%
“…It was recently shown that the response to primary chemotherapy is lower in terms of pCR in ILC compared with IDC, with a greater need for mastectomy for the former [21,22]. Conversely, the outcome of ILC appeared to be more favorable than for IDC [20].…”
Section: Discussionmentioning
confidence: 99%
“…One of the oldest (validated) prognostic and predictive factor is the ER. It was demonstrated that pCR is more likely to occur in patients with ER negative than ER positive disease [30][31][32][33]. Therefore, preoperative chemotherapy may not be the most appropriate preoperative approach for patients with ER positive disease.…”
Section: Discussionmentioning
confidence: 99%